Association between polycyclic aromatic hydrocarbons exposure and current asthma: a population-based study - Zhou Jin; Wen Sun; Guangfa Wang (BMC Public Health)
Abstract Background Polycyclic aromatic hydrocarbons (PAHs) are environmental contaminants that can cause a variety of health problems. This study sought to determine whether there was a relationship between PAHs and current asthma in adults. Methods This cross-sectional study utilized data from the National Health and Nutrition Examination Survey (NHANES) from 2007 to 2016 and employed multifactor logistic regression, subgroup analyses, and smoothed curve fitting to examine the linear and nonlinear associations between PAHs and current asthma. Results A total of 8729 adult participants were included in the study. We found a linear positive association between current asthma and the six PAHs. In the fully adjusted model, log 3-Hydroxyfluorene, log 2-Hydroxyfluorene, and log 1-Hydroxypyrene remained significantly associated with current asthma. Subgroup analyses stratified by smoking status, gender, age, and body mass index (BMI) showed consistent associations between PAHs and current asthma, with some subgroups displaying stronger positive correlations. Specifically, positive correlations between log 1-Hydroxynaphthalene, log 3-Hydroxyfluorene, and log 2-Hydroxyfluorene with current asthma were independently significant in smokers. Among women, log 3-Hydroxyfluorene and log 2-Hydroxyfluorene were also significantly associated with current asthma. In participants with a BMI ≥ 30 kg/m2, log 1-Hydroxynaphthalene, log 2-Hydroxynaphthalene, and log 1-Hydroxypyrene were significantly correlated with current asthma. For individuals aged 20–40 years, log 3-Hydroxyfluorene and log 1-Hydroxypyrene showed independent associations with current asthma, with age modifying the relationship between log 1-Hydroxypyrene and current asthma (p for interaction < 0.05), while p for interaction values in other subgroups were not statistically significant. Additionally, a variable relationship between log 1-Hydroxypyrene and current asthma was identified by smoothing curve fitting. The data suggested that below the inflection point of 1.87, the association fluctuates, while above this point, a linear increase in current asthma is observed, as indicated by a two-piecewise linear regression model. Conclusions We found a positive association between PAHs and current asthma in adults, with a variable relationship between log 1-Hydroxypyrene and current asthma, suggesting that high levels of 1-Hydroxypyrene exposure may increase the risk of current asthma. More prospective studies are needed to confirm our findings.